Performance of the companies taken over by danaharta before and during the financial crisis - Norsalina, binti Hj Salim (Universiti Malaysia Sarawak (UNIMAS), 2002)
This project paper examines performance before and during the financial crime of listed companies which have been taken over by Danaharta Nasional Berhad. This study covers a period of more than 15 years, encompassing four sub-peri of pre-crisis I, during crisis I, pre crisis II and during II experienced by the country. In addition, this study also evaluated the performance of the company listed for more than 10 years which were hit twice by the crisis and analyze they can survived during the first crisis but not during the second crisis